(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The article describe the best library practice adopt in the Navjeevan Law College Library. There are three important components of Libraries are Library users, Library resources and Human resources of Library. To meet the end users demands effectively, the academic libraries need to identify and adopt good practices. Librarians are using their innovative ideas to attract the library user and to convert ‘Non users into users’ and ‘users into active users.’ Law college Libraries need to give services related to case laws and provide different databases to its users. Through Legal Aid Clinic and Child Line Centre sister institute of Library provide various kinds of library services to its users. Computer Lab is available in Library so that use of ICT will became useful to its users. Through best practices adopted in library it increase the value added services for its users.